2001
DOI: 10.1084/jem.194.7.927
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Clonal Expansion of Mutating “Forbidden” (Immunoglobulin Receptor–Deficient) Epstein-Barr Virus–Infected B Cells in Angioimmunoblastic T Cell Lymphoma

Abstract: Angioimmunoblastic lymphadenopathy with dysproteinemia (AILD) is a peculiar T cell lymphoma, as expanding B cell clones are often present besides the malignant T cell clones. In addition, large numbers of Epstein-Barr virus (EBV)-infected B cells are frequently observed. To analyze the differentiation status and clonal composition of EBV-harboring B cells in AILD, single EBV-infected cells were micromanipulated from lymph nodes of six patients with frequent EBV+ cells and their rearranged immunoglobulin (Ig) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 59 publications
6
75
1
2
Order By: Relevance
“…It has been reported that EBV genomes are found in most of the AITL cases 5 and almost all of the cells infected by EBV are B cells showing normal histological findings. 18 In the majority of cases, EBERpositive cells were scattered, but there were sheets of EBVpositive cells in some cases. 19 In spite of such a background, the complication of B cell lymphomas in AITL has been reported to be rare.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that EBV genomes are found in most of the AITL cases 5 and almost all of the cells infected by EBV are B cells showing normal histological findings. 18 In the majority of cases, EBERpositive cells were scattered, but there were sheets of EBVpositive cells in some cases. 19 In spite of such a background, the complication of B cell lymphomas in AITL has been reported to be rare.…”
Section: Discussionmentioning
confidence: 94%
“…The latency pattern for EBV is not known as well, although some have assumed a restricted latency II program similar to that seen in other EBV-associated T-cell lymphoproliferative disorders [93]. This postulation can also be supported by the fact that most of the subsequent EBVassociated B-cell proliferations that follow AILT in few occasions express LMP1 and the EBERs, which is consistent with type II latency [92].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 88%
“…These crippling mutations are almost restricted to the EBVinfected cells and not detected in EBV-negative cells, which assumes a potential influence of EBV on these proliferating cells [93]. Although crippling mutations are also seen in classic Hodgkin lymphoma, HRS cells lack the intraclonal diversity because of the shutdown of the ongoing somatic mutations, in contrast to the EBV-infected B cells in AILT that continue to undergo somatic mutations even with the presence of crippling mutations [94].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 96%
See 1 more Smart Citation
“…Incidence of Ig clonality was highest in AILT (32%), close to the frequencies identified by Smith et al 28 and Lome-Moldonado et al, 35 but higher than reported by Frizzera. 27 In this entity, Ig clonality most likely corresponds to expanded B-cell clones 28,[35][36][37][38] in line with the occurrence of secondary Epstein-Barr viruspositive B-cell lymphoma after AILT. 38,39 Also in T-LGL the association with B-cell proliferations is described.…”
Section: Anaplastic Large Cell Lymphomamentioning
confidence: 99%